2020
DOI: 10.1186/s12884-020-03276-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal mortality and caesarean section in Ethiopia: a national cross-sectional study

Abstract: Background Several studies concluded that there is a reduction of maternal deaths with improved access to caesarean section, while other studies showed the existence of a direct association between the two variables. In Ethiopia, literature about the association between maternal mortality and caesarean section is scarce. This study was aimed to assess the association between maternal mortality ratios and caesarean section rates in hospitals in Ethiopia. Methods Analysis was done of a national maternal health… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…Our results are lower than those found by Ntoimo (2,085 per 100,000 live births) (31), Ousmane (1962 per 100,000 live births in the Labé Regional Hospital in Guinea) (32), and Kamga (1,538.9/100,000 live births in three university hospitals in Yaoundé) (33). However, our results are higher than those found by Sissoko (201.87 per 100,000 live births) (34) and Geleto (149 per 100,000 live births in Ethiopian hospitals) (35). This diversity of results con rms that maternal mortality in hospitals varies according to the context (36).…”
Section: Maternal Mortality Rate In the Reference Hospital Settingcontrasting
confidence: 66%
“…Our results are lower than those found by Ntoimo (2,085 per 100,000 live births) (31), Ousmane (1962 per 100,000 live births in the Labé Regional Hospital in Guinea) (32), and Kamga (1,538.9/100,000 live births in three university hospitals in Yaoundé) (33). However, our results are higher than those found by Sissoko (201.87 per 100,000 live births) (34) and Geleto (149 per 100,000 live births in Ethiopian hospitals) (35). This diversity of results con rms that maternal mortality in hospitals varies according to the context (36).…”
Section: Maternal Mortality Rate In the Reference Hospital Settingcontrasting
confidence: 66%
“…The country has made tangible strides in reducing maternal mortality in the last two decades. The MMR has declined from around 871 deaths in 2000 to 401 deaths in 2017; despite this achievement, there is noticeable variation among regional states [5][6][7]. Due to these regional variations the country has failed to achieve one of the MDGs goals, which had a target of dropping MMR to 267 in 2015 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Facility delivery and caesarian sections were not disrupted (except in Oromia were facility deliveries declined by 7%). It is well known that facility delivery and caesarian sections are key services to reduce maternal complications and deaths and maintaining these services is crucial [30]. Similarly, child vaccinations were generally maintained except in Dire Dawa and Harari regions.…”
Section: Discussionmentioning
confidence: 99%
“…In April 2020, there were about 18% reduction in antenatal care visit in Nigeria and a 17% decline in postnatal care use in Mali [2]. A study conducted in urban Ethiopia found a significant reduction in child vaccination services in urban area especially in Addis Ababa and Harari [30]. However, these reductions occurred only for a few months after the pandemic was declared.…”
Section: Discussionmentioning
confidence: 99%